(untitled)
The research deals with one of the contemporary and important issues; Which has deep roots in political historyFor the major countries, Iraq has a direct impact on the course of political transformations in the Middle East, pIt is the heart of the Greater Middle East project; The transformations taking place in the region and the world as a whole will not happenAway from his expected and decreed role within the international contexts that define the political features of the outside world;Despite what has been written on the subject, it needs a lot of explanation and explanation, because it is covered in more than one articleA formula that corresponds to the international, regional and even local data of the relevant country, and in this matterWe note that Iraq as a country has become the link that brings together all the disparate international trends. to meet onhis land in order to draw future plans; And if the Greater Middle East project is one of the plansTo control the future in the region, this means the presence of players who play their specific roles for them; on meThat its results are in the supreme interest of a country like the United States of America